2011
DOI: 10.1021/om2006479
|View full text |Cite
|
Sign up to set email alerts
|

Modulating the Steric, Electronic, and Catalytic Properties of Cp* Ruthenium Half-Sandwich Complexes with β-Diketiminato Ligands

Abstract: Five different types of β-diketiminate ligands, bearing electrondonating to strongly electron-withdrawing substituents, were synthesized and used in the synthesis of Cp* ruthenium complexes (Cp* = η 5 -C 5 Me 5 ). One series consists of complexes with a covalent Ru III −Cl bond, and the other series features a reduced Ru II center, where the chloride is abstracted by treatment of the corresponding Ru III compounds with Zn or Mg. All compounds were characterized by single-crystal X-ray diffraction, UV−visible s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 134 publications
5
26
0
Order By: Relevance
“…Both complexes 2a (67%) and 2b (using n BuLi, 82%) were readily isolated and appear to be stable at room temperature under a nitrogen atmosphere both in solution and in the solid state. The highly colored nature of 2a and 2b is consistent with previously reported 16-electron Cp*Ru complexes, including Cp*RuL(X), 1,6-8 Cp*Ru(amidinate), 1,13 and Cp*Ru (diketiminate), 14,15 which are typically blue or purple in color. The solution NMR ( 1 H, 13 C, 31 P) spectra of 2a and 2b (benzene-d 6 ) are consistent with their formulation as C s -symmetric, diamagnetic, N-phosphinoamidinate complexes.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…Both complexes 2a (67%) and 2b (using n BuLi, 82%) were readily isolated and appear to be stable at room temperature under a nitrogen atmosphere both in solution and in the solid state. The highly colored nature of 2a and 2b is consistent with previously reported 16-electron Cp*Ru complexes, including Cp*RuL(X), 1,6-8 Cp*Ru(amidinate), 1,13 and Cp*Ru (diketiminate), 14,15 which are typically blue or purple in color. The solution NMR ( 1 H, 13 C, 31 P) spectra of 2a and 2b (benzene-d 6 ) are consistent with their formulation as C s -symmetric, diamagnetic, N-phosphinoamidinate complexes.…”
Section: Resultssupporting
confidence: 89%
“…The Ru−N(2) distance of 2.0734(16) Å in 2b is somewhat elongated relative to that of 2.0458(13) Å in 2a, which can most likely be ascribed to the greater steric demands of the isopropylfunctionalized ligand in 2b. Nonetheless, these Ru−N distances fall within the range observed for crystallographically characterized Cp*Ru(amidinate) (2.073(3) Å) 13 and Cp*Ru(diketiminate) (2.025(6)−2.071(2) Å) 14,15 complexes. The solid-state structures of 2a and 2b are consistent with the C s -symmetric species observed in solution, as indicated by the perpendicular orientation of the P−Ru−N(2) plane relative to the plane of the Cp* ligand.…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…Similar to AIBN, the additive Mg allows the catalyst loading to be reduced dramatically. [9] Recently we have shown that manganese powder can be an interesting alternative to Mg. [10] It should be pointed out that AIBN and Mg have also been used with great success in Cu-catalyzed AT RA reactions. [11] The combination of Cp*RuCl 2 (PPh 3 ) with Mg represents one of the most powerful catalytic systems for AT RA/ATRC reactions described so far.…”
Section: Reducing Agents In Ru-catalyzed Atra Reactionsmentioning
confidence: 99%